2019
DOI: 10.22158/jecs.v3n2p71
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Sense of Belonging of Part-time Faculty within Institutions of Higher Education

Abstract: <p><em>Although part-time faculty positions in higher education continue to increase, reports reveal the lack of acceptance and valuing of part-time faculty across higher education institutions. Yet few qualitative studies explore this phenomenon within academic culture. This exploratory qualitative case study analyzed part-time faculty members’ perceptions of inclusion or exclusion within their higher education institutions. This study was based on interviews with a diverse sample of part-time fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(46 citation statements)
references
References 16 publications
(20 reference statements)
8
38
0
Order By: Relevance
“…4 Additional teaching tasks imply less time for research and may delay completion of the doctorate (Maher et al 2004). At the same time, being employed full-time at the university is shown to be related to a stronger sense of belonging (Ryan et al 2019) to the respective community, thus indicating more reliable contacts which may motivate DDHs to remain in the same sector.…”
Section: Ddhs' Decisionsmentioning
confidence: 99%
“…4 Additional teaching tasks imply less time for research and may delay completion of the doctorate (Maher et al 2004). At the same time, being employed full-time at the university is shown to be related to a stronger sense of belonging (Ryan et al 2019) to the respective community, thus indicating more reliable contacts which may motivate DDHs to remain in the same sector.…”
Section: Ddhs' Decisionsmentioning
confidence: 99%
“…Yet, in more recent years, research has begun examining the interpersonal experiences and integration of part-time faculty into the campus culture (e.g. Culver et al, 2020; Ryan, 2017; Vicente, 2017). In a qualitative study focused on gaining a rich perspective of contingent faculty, Vicente (2017) uncovered that contingent faculty expressed a lack of acknowledgement and relationships with their tenure-track counterparts, though the number of full-time and part-time contingent faculty participants was not clear.…”
mentioning
confidence: 99%
“…In a qualitative study focused on gaining a rich perspective of contingent faculty, Vicente (2017) uncovered that contingent faculty expressed a lack of acknowledgement and relationships with their tenure-track counterparts, though the number of full-time and part-time contingent faculty participants was not clear. Additionally, Ryan (2017) found that part-time faculty members were likely to perceive a sense of belonging when their relational needs were being met. Culver et al (2020) found that part-time faculty members were less likely than full-time faculty, to feel supported by the organization.…”
mentioning
confidence: 99%
“…In Cycle 1 participants identified recognition and community, and lack thereof, as factors that impacted their sense of workplace belonging. Literature illustrates that employees who feel their contributions are recognized are likely to feel valued which leads to an increased sense of workplace belonging (Benito & Scott-Milligan, 2018;Creary, 2020;Gallup 2022;Lampinen et al, 2017Lampinen et al, , 2018McClure & Brown, 2008;Ryan et al, 2019). Cycle 1 participants also described increased silos and a lack of social cohesion resulting from the COVID-19 pandemic as negatively contributing to their sense of belonging.…”
Section: Problem Statementmentioning
confidence: 99%
“…Workplace belonging is defined as an individual's sense of feeling included, accepted, and valued among a particular group (Baumeister & Leary, 1995, as cited in Filstad et al, 2019Jena & Pradhan, 2018;McClure & Brown, 2008). Employees with a strong sense of belonging are likely to demonstrate increased retention (Huppert, 2017;Jena & Pradhan, 2018;Settles et al, 2021) and perceive themselves as members of a cohesive workplace community (Filstad et al, 2019;Lampinen et al, 2017Lampinen et al, , 2018Ryan et al, 2019). Knowledge generated from this study informed those collaborating on the research, the college's workforce, as well as other organizations and higher education institutions examining methods to strengthen workplace belonging.…”
Section: Purpose Of Researchmentioning
confidence: 99%